Unlocking Threshold Concepts: Transforming Student Identities through an International ‘Year‐Out’ Multidisciplinary Design Education Programme - Richardson, Charles; Harrison, Daniel (Design Management Journal, 2024)
Industry demands that graduates excel in their academic disciplines while creatively solving problems and challenges across various contexts, while collaborating effectively as part of a multidisciplinary team. This paper reflects on key learnings and implications from delivery of an innovative and novel “year‐out” multidisciplinary design education programme for third‐year undergraduate students from multiple disciplinary backgrounds. The programme's core aim was to facilitate learning and application of a range of design tools and methods, while concurrently allowing students to apply knowledge and skills from their home disciplines. Bringing together students from a range of disciplines helped to create novel solutions to complex problems while fostering critical thinking, creativity, adaptability, communication and collaboration – key skills for graduate employability. This paper derives and interrogates key learnings associated with two years of programme delivery. With a focus on pedagogical approaches through the lens of Threshold Concepts, we provide recommendations that support students to develop their own agency, to make this transition possible.